Implementasi Proyek Penguatan Profil Pelajar Pancasila Melalui Kurikulum Merdeka Belajar di SMP Negeri 1 Gunung Talang - Nurhidayati, Nurhidayati; Indrawadi, Junaidi; Ananda, Azwar; Moeis, Isnarmi (Journal of Civic Education, 2024)
This study examines the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 1 Gunung Talang. The research was driven by limited dissemination and understanding of the independent learning curriculum, particularly regarding P5. The objective of this research is to analyze the implementation of P5, identify challenges encountered during its execution, and explore strategies to address these challenges. This study employs a qualitative research approach with a descriptive method. Informants were selected using purposive sampling, and data were collected through interviews, observations, and documentation. Data validity was ensured using triangulation of sources, while analysis involved data reduction, data presentation, and conclusion drawing. The findings reveal that P5 is implemented for grade VII students at SMP Negeri 1 Gunung Talang. However, challenges include insufficient socialization of the program, difficulties in developing project modules, and issues in allocating time for project execution. To address these issues, the school has conducted teacher training on the P5 framework within the independent learning curriculum and facilitated discussions among teachers involved in class projects to refine time management strategies. Future studies should explore the long-term impacts of P5 implementation on student character development and academic performance. Additionally, research could investigate the integration of P5 across different grade levels to assess its broader applicability and effectiveness. Quantitative studies measuring the correlation between teacher training effectiveness and project outcomes would also provide valuable insights. Furthermore, examining the role of parental involvement and community support in enhancing P5 implementation may offer a more comprehensive understanding of its success factors.